The Interorganizational Learning Dilemma: Collective Knowledge Development in Strategic Alliances - Larsson, Rikard; Bengtsson, Lars; Henriksson, Kristina; Sparks, Judith (Organization Science, 1998)
Alliances are volatile key components of many corporations' competitive strategies. They offer fast and flexible means of achieving market access, scale economies, and competence development. However, strategic alliances can encounter difficulties that often lead to disappointing performance. The authors suggest that the way partners manage the collective learning process plays a central role in the success and failure of strategic alliances. Present understanding of interorganizational learning primarily focuses on how the individual organization can be a “good partner” or try to win the internal “race to learn” among the partners. The interorganizational learning dilemma is that (1) being a good partner invites exploitation by partners attempting to maximize their individual appropriation of the joint learning, and (2) such opportunistic learning strategies undercut the collective knowledge development in the strategic alliance. The authors develop a framework for understanding the dilemma through consideration of trade-offs between how collective learning is developed in alliances and how the joint learning outcomes are divided among the partners. They create a typology of five different learning strategies based on how receptive as well as how transparent an organization is in relation to its partners. The strategies are: collaboration (highly receptive and highly transparent); competition (highly receptive and nontransparent); compromise (moderately receptive and transparent); accommodation (nonreceptive and highly transparent); and avoidance (neither receptive nor transparent). Interorganizational learning outcomes are proposed to be the interactive results of the respective partners' type of adopted learning strategy. By synthesizing strategic alliance, organizational learning, collective action, and game theories, the framework contributes to understanding the variety in alliance development, performance, and longevity. Interorganizational learning is likely to be hindered by lack of either motivation or ability to absorb and communicate knowledge between the partner organizations. The dynamics of power, opportunism, suspicion, and asymmetric learning strategies can constitute processual barriers to collective knowledge development. In contrast, prior related interaction between the partners, high learning stakes, trust, and long-term orientation are likely to empower the collective learning process. Comparison of previous case studies and surveys of interorganizational learning provides partial empirical support for the proposed framework. The comparison also indicates several omissions in previous research, such as failure to consider either how receptive or how transparent the partners are, the interaction between their learning strategies, and their dynamic processes over time. Because these omissions are due partly to the methodological limitations of traditional case studies and crosssectional surveys, the authors suggest a bridging case survey design for a more comprehensive test of their interactive, dynamic, and situational framework.